Reliability assessment of steel slag and construction waste backfill for reinforced earth structures using response surface method - Sarkar, Sanjana; Hegde, Amarnath (Soils and foundations, 2025)
The study investigates the potential of two waste materials, steel slag and construction and demolition waste (CDW) as backfills for mechanically stabilized earth (MSE) walls. The design of MSE walls traditionally relies on factors of safety (FS) derived from empirical assessments, leading to uncertainties in soil behaviour and stability evaluations. To address this, probabilistic analyses were conducted to evaluate the suitability of slag and CDW backfills. The performance of MSE walls with various backfills was compared through FLAC-2D finite difference simulations. The findings show that substituting sand with slag or CDW significantly reduced the horizontal facing displacement by 83 % and 86 %, respectively. Lower reinforcement strains were also observed with slag and CDW backfills compared to sand. Further, probabilistic studies were conducted on the numerical model using the response surface method (RSM). The reliability index of the MSE wall model was determined using RSM considering uncertainties in soil properties and reinforcement characteristics. At a specified displacement limit, the probability of failure of walls filled with slag and CDW was significantly lower than that of walls filled with sand. Partial safety factors pertaining to friction angle, unit weight and geogrid stiffness were higher with slag and CDW backfills, suggesting reduced risk of failure associated with the alternate backfills. These findings emphasize the potential benefits of using slag and CDW in MSE walls, highlighting the improved performance of these alternate backfills over conventional backfill.